2012
DOI: 10.2176/nmc.52.41
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Post-traumatic Pseudoaneurysmal Formation of the Intracranial Ophthalmic Artery After Closed Head Injury -Case Report-

Abstract: A 42-year-old male presented with a rare case of delayed aneurysmal formation of the intracranial ophthalmic artery after closed head injury manifesting as subarachnoid hemorrhage. Initial magnetic resonance angiography revealed no aneurysmal formation, but angiography 7 days after the injury demonstrated an intracranial ophthalmic artery aneurysm. Follow-up computed tomography angiography demonstrated enlargement of the aneurysm. The aneurysm was successfully treated by surgical resection. Histological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“… 10) In the supraclinoid segment, the carotid artery transitions from a relatively fixed structure in the skull base and cavernous sinus to a relatively mobile structure as it ascends into the cisternal spaces. Researchers believe that either movement of the supraclinoid segment against the anterior clinoid process or stretching of the carotid artery at this transition zone leads to the formation of such an aneurysm, 7 , 12 , 13) and this mechanism apparently applies to our case.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“… 10) In the supraclinoid segment, the carotid artery transitions from a relatively fixed structure in the skull base and cavernous sinus to a relatively mobile structure as it ascends into the cisternal spaces. Researchers believe that either movement of the supraclinoid segment against the anterior clinoid process or stretching of the carotid artery at this transition zone leads to the formation of such an aneurysm, 7 , 12 , 13) and this mechanism apparently applies to our case.…”
Section: Discussionmentioning
confidence: 56%
“…Traumatic pseudoaneurysm occasionally regresses in size or spontaneously disappear, 7 , 9 , 11) but they also have a high incidence of rupturing. Therefore, surgery or endovascular treatment is necessary as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…1) However, there are reports of rare origins, such as the basilar and middle meningeal arteries. 4,5) A review of the literature revealed only six reported cases of traumatic pseudoaneurysm of the OphA and its tributaries (Table 1), 2,3,[6][7][8][9] only two of which had epistaxis. 2,3) In one case, a gunshot wound had injured the cranial base and the OphA.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs most commonly in the peripheral arteries or the internal carotid artery (ICA) in a closed head injury. 3 5 9 10 11 14) Traumatic ophthalmic artery aneurysms are particularly rare. We present a case of endovascular treatment of traumatic ophthalmic artery aneurysm which had grown late after closed head injury.…”
Section: Introductionmentioning
confidence: 99%